Combined Al and C alloying enables mechanism-oriented design of multi-principal element alloys: Ab initio calculations and experiments. (15th March 2020) - Kies, Fabian; Ikeda, Yuji; Ewald, Simon; Schleifenbaum, Johannes H.; Hallstedt, Bengt; Körmann, Fritz; Haase, Christian
Graphical abstract: Abstract: Density functional theory (DFT) calculations were performed on Alx Cy CoFeMnNi multi-principal element alloys (MPEAs) to understand the influence of Al and C on the stacking-fault energy (SFE). C addition to CoFeMnNi resulted in increased SFE, while it decreased in Al-alloyed CoFeMnNi. For experimental verification, Al0.26 Cy CoFeMnNi with 0, 1.37 and 2.70 at% C were designed by computational thermodynamics, produced by additive manufacturing (AM) and characterized by tensile tests and microstructure analysis. Twinning-induced plasticity (TWIP) was enhanced with increased C, which confirmed a decreased SFE. The combination of these methods provides a promising toolset for mechanism-oriented design of MPEAs with advanced mechanical properties.